Natural organic matter removal by conventional water treatment in a tropical river - Jiménez-Antillón, Joaquín (2022)
In Costa Rica, the effectiveness of the water purification process by conventional method is evaluated primarily in terms of color and turbidity removal and not of natural organic matter (NOM), which, when chlorinated, can form potentially carcinogenic disinfection by-products (DBPs) such as trihalomethanes (THMs). Water from the Jorco river treatment plant, in San José, was monitored, monthly, from March 2015 to February 2016, at each stage of the treatment. Total (TOC) and dissolved (DOC) organic carbon, ultraviolet absorption at 254 nm (UV254) and the specific UV absorbance (SUVA) were quantified. During the hole period, TOC and DOC from crude water ranged between 0,42 ± 0,01 mg-C/L to 0,96 ± 0,19 mg-C/L. UV254 absorbance and SUVA ranged from 0,0106 cm-1 and 2,71±0,55 L/mg-m (dry season) to 0,250 cm-1 and 2,06±1,16 L/mg-m (rainy season), indicating a mixture of aromatic and aliphatic substances in water. In the treatment system, the coagulation-settling stage had the greatest removal efficiency with close to 21% and 23% for TOC and DOC, respectively, during both seasons. The total purification system removed 51% of UV254 and 32% of SUVA, showing the removal of aromatic NOM, a precursor of DBPs. UV254 quantification showed a good correlation with NOM (>99% in accordance with Pearson´s correlation coefficient), indicating its possible use as a substitute for TOC and DOC analysis. Considering the type and low concentration of NOM in raw water together with the efficiency of the treatment, THMs monitoring in the distribution system, confirmed a total trihalomethane (TTHMs) production close to 10 µg/L, well below the national regulations (460 µg L-1 as total trihalomethanes).